Implementasi Program Pelayanan One Day Service dalam Meningkatkan Kualitas Pelayanan Badan Pertanahan Nasional Kota - Andani, Ariska Tri Viky; Setyowati, Endah; Amin, Fadillah (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
Public service is one of the important things that becomes a benchmark in the implementation of government administration as a manifestation of creating quality public services. The problem in public service is a burden for the government because many complaints are received by the government on the implementation of public services, especially in the field of land, services about land services that seem convoluted and require a long time. Head of Land Agency Regulation No. 1 of 2010 as an effort to respond to poor service by the National Land Agency of the Republic of Indonesia through accelerated public service programs in the land sector, one of which is One Day Service for Land Services or one-day service that can be carried out throughout the Agency's work area National Land all over Indonesia. It is expected that this program can improve thequality of public services in the field of land so that public services in the land sector become a quality and effective and efficient service.